Grocery garbage: food waste and the rise of supermarkets in the mid-twentieth century United States. Issue 1 (2nd January 2019) - Zeide, Anna
ABSTRACT: Food waste and its disposal have long been central problems of food distribution and retailing. The supermarket revolution in the United States, beginning in the 1930s, introduced both new opportunities and new challenges. As American supermarkets grew bigger, they cut losses in some areas, but also saw increasing waste. Operators had to deal with concerns about consumers handling produce, higher aesthetic standards that led stores to discard more edible produce, overstocking, and more trimming with the rise of prepackaging. The growing piles of garbage that the new large supermarkets produced were directed toward one of the methods of disposal that was gaining ground in mid-twentieth century America. Public works and public health officials championed sanitary landfills, hog feeding operations, garbage grinders, and incineration, despite all of the potential costs associated with each method. Heightened awareness of the environmental and public health costs of water and air pollution led citizens and leaders to push back against these disposal systems, often displacing them onto marginalised communities.